The role of effective communication and collective intelligence in digital transformation of a company - V. I. Abramov; D. A. Churkin (Вестник университета, 2024)
The subject of the study is the role of effective communications and the mechanism of meaning emergence in the collective mind of a complex commercial social and technical system. We have synthesized the provisions of traditionally studied separately spheres of knowledge such as the communication theory, collective intelligence, corporate culture management, and motivation theory in the context of digital transformation of companies. The analysis of these concepts together provides a deeper understanding of the knowledge acquisition processes necessary to improve digital transformation effectiveness. The paper formulates the effective communication management principles that contribute to tacit knowledge identification and its successful formalization. We have proposed a distinction of related terms such as data, information, knowledge, understanding, wisdom, and vision. The applied nature of the study is to deepen the understanding of the mechanism of innovative ideas emergence and to propose measures to minimize the risks of managing the communication system in organizations. The following approaches have been considered: values management, emotional intelligence development, decision-making routes and motivation mechanisms personalization, communication formats specification. The article may be useful for researchers whose interests include innovative trends in management, entrepreneurial activity development and enterprises digitalization effectiveness. The study results may be useful for managerial practitioners who develop and implement strategies for enterprises innovative development.